Limbah Kulit Pisang Sebagai Alternatif Pengganti Pewarna Sintetis Pada Bedak Tabur - Tritanti, Asi; Pranita, Ika (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
This research aims at finding out (1) the process of making banana peel powder that can be used as an alternative for synthetic dyes, (2) the characteristics of banana peel powder product, (3) the result of banana peel coloring powder compared to synthetic coloring, yellow metanil. This study can be categorized as experimental study using two groups of subjects; one group was given a specific treatment while another was used as the control group. The data of the study were collected using labsheets, questionnaires and laboratory testing. Data analysis technique used descriptive statistics, T-Test, and Anova Test. The findings showed that control dye had a bright yellow color while the samples treated with A2 had a dark yellow. Tukey test of A2 treatment showed the score of Tukeytable 3,25 3,80. It means color intensity from A2 treatment was similar to the control group. The result of laboratory testing showed that the sample of banana peel powder with A2 treatment had the water content of 3,72% in the first test and 3,87 in the second test. Meanwhile, pH value was 6,7 in the first test and 6,6 in the second test.